Radiation and Buoyancy Effects on MHD Stagnation Point Flow of Micropolar Fluids due to a Porous Stretching Sheet: Radiation and Buoyancy Effects on MHD Flow of Micropolar Fluids - Waqas, Hassan; Hussain, Sajjad; Khalid, Shamila (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Computational investigation for buoyancy and radiation effects on the magneto hydrodynamics stagnation point flow of micropolar fluids has been made to study the kinematics and temperature distribution under the influence of virtual parameter of physical importance. The similarity functions have been used to obtain the ordinary differential equations for non-linear partial differential model of the problem. The results have been computed by Mathematica software and presented the graphs of microrotation, temperature and velocity.